Care/curation of the self, care/curation of the world: Ways to perform reciprocity: modos de performar la reciprocida (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This performative writing mobilizes, as an artistic position, a notion of cure as care and as a movement. It does that operating a curation of the affections that occurs in the act of looking at/repairing [reparar] what appears in each situation, a perception-action of the affections that composes and recomposes figures of subjectivity in co-breeding relationship with the world. Here the intrinsic relation between creation in art and possibilities of sensitive learning makes itself present, as an ethical-aesthetic-political life, an art of existence. It is a tactic of re-existence which is invented by questioning the modes of operation of the usual logic of debt / doubt and which is established by the subversion of that system in the form of a gift cycle: giving-receiving-giving.
Keywords: Gift; Curation of the affections; Propositions in performance; Body-world; Art-life